Isolation and Crystallographic Characterization of Two, Nonisolated Pentagon Endohedral Fullerenes: Ho3N@C2(22010)‐C78 and Tb3N@C2(22010)‐C78. Issue 54 (5th August 2019) - Stevenson, Steven; Rothgeb, Amanda J.; Tepper, Katelyn R.; Duchamp, James; Dorn, Harry C.; Powers, Xian B.; Roy, Mrittika; Olmstead, Marilyn M.; Balch, Alan L.
Abstract: Purified samples of Ho3 N@ C 2 (22010)‐C78 and Tb3 N@ C 2 (22010)‐C78 have been isolated by two distinct processes from the rich array of fullerenes and endohedral fullerenes present in carbon soot from graphite rods doped with Ho2 O3 or Tb4 O7 . Crystallographic analysis of the endohedral fullerenes as cocrystals with Ni(OEP) (in which OEP is the dianion of octaethylporphyrin) shows that both molecules contain the chiral C 2 (22010)‐C78 cage. This cage does not obey the isolated pentagon rule (IPR) but has two sites where two pentagons share a common C−C bond. These pentalene units bind two of the metal ions, whereas the third metal resides near a hexagon of the cage. Inside the cages, the Ho3 N or Tb3 N unit is planar. Ho3 N@ C 2 (22010)‐C78 and Tb3 N@ C 2 (22010)‐C78 use the same cage previously found for Gd3 N@ C 2 (22010)‐C78 rather than the IPR‐obeying cage found in Sc3 N@ D 3 h ‐C78 . Abstract : Purified samples of Ho3 N@ C 2 (22010)‐C78 and Tb3 N@ C 2 (22010)‐C78 have been isolated from fullerenes and endohedral fullerenes present in carbon soot from graphite rods doped with Ho2 O3 or Tb4 O7 . Crystallographic analysis of the endohedral fullerenes as cocrystals with Ni(OEP) shows that both molecules contain the chiral C 2 (22010)‐C78 cage, which does not obey the isolated pentagon rule but has two sites where two pentagons share a common C−C bond (see figure).